Myoepithelial carcinoma with rhabdoid features in the maxillary sinus: Immunohistochemical and in situ hybridization analysis of a rare case - Silveira, Heitor Albergoni [UNESP]; Almeida, Luciana Yamamoto [UNESP]; Weege Nonaka, Cassiano Francisco; Alves, Pollianna Muniz; Ribeiro-Silva, Alfredo; Leon, Jorge Esquiche (Elsevier B.V., 2019)
Myoepithelial carcinomas of the head and neck are often located in the major salivary glands, notably in the parotid glands, being less frequent in the minor salivary glands. Noteworthy, myoepithelial carcinoma in the maxillary sinus is extremely rare. In fact, only five cases have been previously published to date. Here, we present, for the first time, a detailed immunohistochemical and in situ hybridization analysis of a SMARCB1 (INI-1)-intact myoepithelial carcinoma with rhabdoid features, expanding the histopathological spectrum of highgrade sinonasal carcinomas.
Keywords: Myoepithelial carcinoma; Sinonasal carcinoma; Rhabdoid phenotype; Maxillary sinus; Immunohistochemistry; In situ hybridization